Basics of continuous renal replacement therapy in pediatrics - Jacob C. John; Sara Taha; Timothy E. Bunchman (The Korean Society of Nephrology, 2019)
In the last three decades, significant advances have been made in the care of children requiring renal replacement therapy (RRT). The move from the use of only hemodialysis and peritoneal dialysis to continuous venovenous hemofiltration with or without dialysis (continuous renal replacement therapy, CRRT) has become a mainstay in many intensive care units. The move to CRRT is the result of greater clinical experience as well as advances in equipment, solutions, vascular access, and anticoagulation. CRRT is the mainstay of dialysis in pediatric intensive care unit (PICU) for critically ill children who often have hemodynamic compromise. The advantages of this modality include the ability to promote both solute and fluid clearance in a slow continuous manner. Though data exist suggesting that approximately 25% of children in any PICU may have some degree of renal insufficiency, the true need for RRT is approximately 4% of PICU admissions. This article will review the history as well as the progress being made in the provision of this care in children.